The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsnano.5b02840
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Thermal and Light-Induced Spin-State Switching of an Fe(II) Complex in Direct Contact with a Solid Surface

Abstract: Spin crossover (SCO) complexes possess a bistable spin state that reacts sensitively to changes in temperature or excitation with light. These effects have been well investigated in solids and solutions, while technological applications require the immobilization and contacting of the molecules at surfaces, which often results in the suppression of the SCO. We report on the thermal and light-induced SCO of [Fe(bpz)2phen] molecules in direct contact with a highly oriented pyrolytic graphite surface. We are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
175
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(204 citation statements)
references
References 29 publications
11
175
2
7
Order By: Relevance
“…• Charge order of high-Tc Superconductors (Blanco-Canosa et al, 2013;Comin et al, 2014;da Silva Neto et al, 2014;Fink et al, 2009;Ghiringhelli et al, 2012) • Coupling of electronic / lattice degrees of freedom in multiferroic materials (Glavic et al, 2013;Partzsch et al, 2011;Schierle et al, 2010;Schmitz-Antoniak et al, 2013;Skaugen et al, 2015) • Microcrystals of novel materials (Leininger et al, 2011;Matsuda et al, 2015) • Interfacial electronic properties in heterostructures (Frano et al, 2013;Wadati et al, 2009) • Element-speci c magnetic hysteresis loops (Radu et al, 2012) • Single molecular magnets (Bernien et al, 2015;Hermanns et al, 2013) • Electronic depth pro les • Electronic ground states and phase transitions in correlated materials (Schmitz et al, 2014;Strigari et al, 2013;Willers et al, 2012Willers et al, , 2011 • Magnetic clusters in carbon nanotubes (Shiozawa et al, 2015) • Nanoparticles for medical applications (Graf et al, 2015) • Magnetic semiconductors (Khalid et al, 2014) …”
Section: Applicationsmentioning
confidence: 99%
“…• Charge order of high-Tc Superconductors (Blanco-Canosa et al, 2013;Comin et al, 2014;da Silva Neto et al, 2014;Fink et al, 2009;Ghiringhelli et al, 2012) • Coupling of electronic / lattice degrees of freedom in multiferroic materials (Glavic et al, 2013;Partzsch et al, 2011;Schierle et al, 2010;Schmitz-Antoniak et al, 2013;Skaugen et al, 2015) • Microcrystals of novel materials (Leininger et al, 2011;Matsuda et al, 2015) • Interfacial electronic properties in heterostructures (Frano et al, 2013;Wadati et al, 2009) • Element-speci c magnetic hysteresis loops (Radu et al, 2012) • Single molecular magnets (Bernien et al, 2015;Hermanns et al, 2013) • Electronic depth pro les • Electronic ground states and phase transitions in correlated materials (Schmitz et al, 2014;Strigari et al, 2013;Willers et al, 2012Willers et al, , 2011 • Magnetic clusters in carbon nanotubes (Shiozawa et al, 2015) • Nanoparticles for medical applications (Graf et al, 2015) • Magnetic semiconductors (Khalid et al, 2014) …”
Section: Applicationsmentioning
confidence: 99%
“…

for the investigation of the interplay between molecular spinstate switching and charge transport in SCO materials. [ 17,25,27,[30][31][32][33][34] The bulk powder of 1 displays a rather abrupt, cooperative, fi rst-order thermal spin transition around 165 K with a very narrow hysteresis, while the vacuum-deposited fi lms exhibit a very gradual (i.e., weakly cooperative) thermal spin crossover between ≈100 K (LS) and 200 K (HS). To this aim we have chosen the [Fe(H 2 B(pz) 2 ) 2 (phen)] SCO complex 1 (H 2 B(pz) 2 = dihydrobis(pyrazolyl)borate and phen = 1,10-phenanthroline, see Figure 1 a), [ 29 ] which can be deposited on surfaces by thermal evaporation.

…”
mentioning
confidence: 99%
“…To this aim we have chosen the [Fe(H 2 B(pz) 2 ) 2 (phen)] SCO complex 1 (H 2 B(pz) 2 = dihydrobis(pyrazolyl)borate and phen = 1,10-phenanthroline, see Figure 1 a), [ 29 ] which can be deposited on surfaces by thermal evaporation. [ 33,34 ] Previous X-ray diffraction studies revealed that the fi lms are amorphous, [ 30 ] which explains probably the loss of the fi rst-order nature of the spin transition (i.e. Both the powder and fi lm samples are known to exhibit also light-induced excited spin-state trapping (LIESST) phenomenon with a long-lived metastable HS state below ≈50 K. [ 30 ] Interestingly, the spin crossover properties of the fi lms are not much altered by the fi lm thickness from the micrometer scale down to the isolated molecule level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is only recently that supported examples have emerged, starting from 3-dimensional (3D) materials with thin-films grown on gold. 11,16,17 0D systems followed based on single SCO molecules, [18][19][20][21][22][23][24] or molecular junctions. 25 However, 2D monolayer organized networks exhibiting SCO behavior have not been reported so far.…”
mentioning
confidence: 99%